Genitourinary Syndrome of Menopause - Valadares, Ana Lúcia Ribeiro (2022)
Key points • Genitourinary syndrome is a complex chronic syndrome with multiple changes in genitourinary tissues in response to menopausal loss of estrogen. • Symptoms range from mild to severe and may have effects on genitourinary and sexual function, relationships and quality of life. • Treatments can be non-hormonal with lubricants and moisturizers or with vaginal or systemic estrogen therapy. • A multidisciplinary approach may be needed when there are complex problems, including sexual dysfunction. • The gynecologist is in a unique position to sensitively discuss the symptoms of genitourinary syndrome, advise, educate and treat appropriately, providing long-term follow-up.